The impact of thin capitalization rules on shareholder financing - Alexandra Maßbaum; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2008)
From a tax planner's point of view, it is often attractive to choose debt over equity financing. As this has led to an increase of debt financing of corporations, many countries have introduced thin capitalization rules to secure their tax revenues. We analyze the influence of section 8a of the German Corporate Tax Code on corporate capital structure decisions. Furthermore, the impact of the new interest barrier is taken into consideration. The existence of the Miller equilibrium as well as definite financing effects depend significantly on the fraction of long-term debt, of substantial shareholders and when capital gains are realized.
Keywords: H25; H21; G32; 330; business taxation; capital structure; interest barrier; Miller equilibrium; share holder financing; thin capitalization rules